Rekonstruksi Hukum Siber di Indonesia dalam Perspektif Negara Hukum Digital: Sebuah Keniscayaan Regulasi Adaptif - Gilang Rizki Aji Putra (BULETIN ADALAH, 2020)
Digital transformation has reshaped legal relations, creating borderless cyberspace beyond national jurisdiction. This study examines challenges in Indonesia’s cyber law and proposes a digital rule of law approach. It finds current regulations are fragmented, reactive, and often create legal uncertainty. Key areas for reform include personal data protection, liability for digital content, and online dispute resolution. The study concludes that beyond legal reform, adaptive and rights-based regulation is needed, supported by a cyber omnibus law and stronger digital literacy among law enforcement.  Keywords: Digital Rule of Law, Cyber Law Reconstruction, Legal Certainty, Personal Data, Omnibus Law